Identifikasi Non-Added Value Activity Dalam Proses Pemeriksaan Substantif Permohonan Paten Menggunakan Value Stream Mapping - Muslim, Muslim; Ichwan, Muhammad Nur; Ikatrinasar, Ikatrinasar; Fitri, Zulfa (Program Studi Teknik Industri, Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
The process of substantive patent examination which is complicated and takes a long time is one of the reasons the inventor is